Testes funcionais como marcadores de severidade e prognóstico de mortalidade em pacientes com doença pulmonar obstrutiva crônica - Dourado, Izadora Moraes (2023)
This dissertation consisted of 2 studies that will be described below: Study I, entitled “Is the six-minute step test able to reflect the severity and symptoms based on the CAT score? aimed to evaluate 1) whether the six-minute step test is associated with the Chronic Obstructive Pulmonary Disease (COPD) Assessment Test (CAT) scores and forced expiratory volume in one second (FEV1); and 2) compare induced physical exercise considering different severities based on CAT scores. This is a cross-sectional study in which 59 patients with COPD were evaluated. The groups were stratified according to the following cutoff points: CAT <10 (little impact) n= 22; CAT 11-20 (moderate impact) n=20; CAT <20 (great impact) n=17. During the 6-minute step test (TD6) the individuals were instructed to go up and down a single step with a height of 20 centimeters (cm). Comparing the groups in terms of performance on the 6MWT, the number of climbs on the step was significantly higher in the CAT <10 group when compared to the CAT >20 group, the HR variation between rest and peak exercise (∆ HRpeak - rest) was lower in the CAT>20 group compared to the CAT<10 group and the CAT 11-20 group. We found direct relationships between the number of ascents and descents on the 6MWT vs the CAT score (r=0.35, p=0.007); and TD6 vs degree of obstruction %FEV1 (r-0.46, p=0.002) We found a linear regression model in which FEV1 (L) and CAT score influenced 29% of the TD6 performance. Therefore, the six-minute step test may provide a valid measure of health status in COPD patients with mild to moderate degrees of obstruction based on the CAT score, which also reflects symptom severity as determined by lung function %FEV1 and FEV1 (L). In addition, the severity of COPD represented by FEV1 and the CAT score influenced the performance of the 6-minute step test by 29%. Our findings may have important implications for the clinical evaluation of these patients, as well as for rehabilitation programs. Study II, entitled “Distance covered in the six-minute walk test in patients with COPD as a predictor of mortality”, aimed to: 1) evaluate the functional capacity through the 6MWT considering the performance obtained in three quartiles of distance walked ( good/moderate/poor) in a larger sample of patients with different degrees of obstruction (mild, moderate, severe and very severe); 2) to verify their impact as predictors of survival in a 24-month follow-up in patients with COPD. This is a 24-month cohort, in which 118 patients with COPD were evaluated. The groups were stratified according to the distance covered in the six-minute walk test (6MWT) as follows: group 1, 6MWT (mean 485-371m); 39 in group 2, 6MWD (mean 370-260m); 40 patients in group 3, 6MWD (mean >259m). Subjects were instructed and encouraged (to walk as far as possible in 6 minutes. We found that more severe patients, as expected, had worse performance in the 6MWT (P<0.05). The CAT questionnaire score was higher for the group 3 had the worst performance in the 6MWT, this score being compatible with more symptomatic and more limited patients. Group 3 (<259m) had the worst performance, mostly composed of individuals classified as severe and very severe by the criteria of the GOLD (p<0.001) and also had higher CAT scores and, consequently, worse clinical impact of COPD (p<0.001). Among the correlations obtained, performance in the 6MWT was associated with higher CAT scores (R= -0.344 , p<0.001) FEV1 was positively correlated with 6MWT performance (R=0.319 and p=0.001). m, were those with the lowest probability of survival, long rank: p=0.001. However, our findings showed that the distance covered in the 6MWT has a predictive value of two-year mortality, even considering a wide spectrum of COPD severity. The worst performance in the 6MWT is associated with greater desaturation, worse HR recovery and more symptoms during physical exercise. Distance walked was also closely associated with greater disease severity and worse CAT scores.